Tolu Bommalu Kattu. Omrids af skyggespillet i Andhra Pradesh - Roed, Niels (Kuml, 1971)
»Tolu Bommalu Kattu«. The shadow play in Andhra Pradesh This article is based on a study of the present status of certain forms of Indian folk drama, carried out during a 6 months' stay in India 1970. Puppet shows and shadow plays were found to be those forms of popular drama, also called »village theatre«, which are nearest extinction. Regular performances in these media are no longer held and a study of their mutual relations and connection with classical theatre in India is therefore urgently necessary. The origin of the shadow play seems to be shrouded in obscurity. The German scholars Richard Pischel (Die Heimat des Puppenspiels, 1900) and Georg Jacob (Geschichte des Schattentheaters, 1925) advanced the theory that it originated as an art form in India and thence passed eastwards to Indonesia, Thailand, Cambodia and Malaysia and westwards by way of Iran to Turkey and North Africa. Shadow plays in the former regions exhibit certain common features, the most prominent being the community of theme, all forms having incorporated themes from the Indian epics of the Ramayana and Mahabharata. Tolu Bommalu Katu means in Telugu »dolls cut out of leather« and is the name for the shadow play doll found in the state of Andhra Pradesh in Southern India. Related forms of shadow play are found in the neighbouring states of Tamil Nad and Mysore, while the shadow play in Kerala and Orissa seems to differ essentially from the one current in Andhra Pradesh. The shadow play in Andhra Pradesh is believed to have a long tradition behind it. It was patronized by the princely families Satavahanas, Pallavas and Chalukyas and reached a height under King Kona Bhudha Reddy in the 16th century with the production of »Ramayana Ranganathana«, a manuscript in Telugu designed exclusively for the medium. At this stage of development, special troupes of shadow players consisting of puppeteers, singers, scene painters and stage hands were organized. With regard to size, mobility and translucence, the shadow dolls of Andhra Pradesh are remarkable. They may be up to 2 m high and are thus the largest shadow puppets known; normal human stature is common in this theatrical form. As the Andhra Pradesh puppet appears today, it is probably the result of a long development, the different stages of which are not yet clear. Its mobility is unique, the various parts of the body being cut out separately and connected by strings. Rama (fig. 4) thus consists of 12 parts. Leather stills, which do not contain movable elements or where perhaps only an arm can be moved (fig. 8), are also employed, however. Traditionally, the puppeteers had to be skilled in all the processes involved in doll construction: treatment of the leather, figure cutting, and decoration by means of perforation and painting. The figures were made of parchment-like, translucent leather obtained from deer, buffalo or goat skin. Tradition dictates that deerskin be used for gods and royalty, buffalo skin for demons, and goatskin for heroes and ordinary people. Today, however, goatskin is the basic material. Since the demand for this form of entertainment is rapidly declining, new shadow puppets are seldom made. The troupe visited in Andhra Pradesh in connection with this study was thus in possession of only a couple of scraps of leather and a little paint, whereas their cutting and perforation tools were intact. Its members were creative artists, able to cut figures in prepared leather without using patterns (fig. 3). The figures are highly stylized, and rules have been developed for the characterization of the persona of the plays. Thus gods, heroes and kings must be furnished with noble brows, straight noses and thin lips, whilst demons have protruding eyes, thick lips, mouths full of long sharp teeth and massive, clumsy and aggressive bodies (fig. 7). Spiritual and physical power, refinement and vulgarity are contrasted in a simple but sophisticated manner. Perforation of the leather is an important part of the manufacturing process. The figures do not throw a massive shadow onto the screen but, when they are most artistically executed, a figure of delicate tracery. In this play on light and shade lies much of the character of the medium. The perforation suggests the pattern and drape of the costume, jewels and other ornaments, and flowers. Demons are as a rule devoid of perforation. On account of the translucence of the leather, the colour is projected onto the screen. An oil lamp was particularly suited to transmit the original natural colours black, red, green and their intermixtures. In the course of the last fifty years the ancient colour tradition has been abandoned in favour of artificial colours. Garish colouring may thus be found in the new puppets, just as old ones have often been painted over with artificial colour. In recent years, the light source has also been changed; petromax lamps, which give a cold bluish light, are now used. It is possible to regard the shadow play as a specific drama form compounded of theatrical elements of a special kind. A shadow play performance in Andhra Pradesh will comprise the following components: light source, screen, stage, doll manipulation, sound and sound effects, song and instrumental music, and fable and its ritual and religious meaning. In the Indian shadow play, the dolls are not visible to the spectators, only their shadows, in contrast to Wayang kulit, the Javanese shadow play. If shadow plays are regarded as a branch of puppetry, the shadow doll is a rod puppet. Edward Craig's theories on the » Ueber marionette« have caused several students of the theatre to concern themselves with the properties of the theatre puppet. Marjorie H. Batchelder's thesis, Rod-puppets and the Human Theatre, 1947, in which the language of puppet gestures is dealt with, may be referred to. Sign-language is also the language of the shadow puppet, especially in Andhra Pradesh, where the various parts of the body are separate and connected by strings, arms and hands thus having a unique mobility, and where the head can move independently of the body. A cleft bamboo cane runs from head to crotch, and thinner canes control the arms and hands. The female dancer is the puppet with the greatest mobility. Two puppeteers are necessary if the expressive possibilities of this brilliantly contrived doll are to be used to full effect. In order to synchronize the doll's movements with the sound, the puppeteers have to dance and jump at the same time as they provide the song and dialogue. Behind the screen, they dance in the classical Kuchipudi style, unseen by the spectators, thus transferring their movements and steps to the doll. The play is performed in the open air, usually in the area in front of the temple, on a covered platform erected for the occasion. The screen, consisting of two white saris pinned together, is between 3 and 8 m long and between 2 and 3½ m high. There is room in the booth for the six to ten members of the troupe to act as puppeteers, singers and instrumentalists. The shadow play is, like most kinds of original Indian folk drama, a variety of dance drama, as the performance is a mixture of instrumental music, song, dance and action. Chorus alternates with solo singing, dialogue and monologue. The puppeteer has to adapt his voice to each doll and up to fifty different dolls may be involved in one performance. The mridangam drum is the most important instrument in the ensemble, in which cymbals and harmonium also feature. During battle scenes, sound effects are provided by the puppeteers' tramping on the floor of the stage, which is raised ½ m from the ground and thus serves as an enormous xylophone. The leader of a shadow play troupe is called sutradhar. This term demonstrates a connection between Indian folk theatre and Sanskrit theatre according to the ancient treatise »Natya Sastra«. The art is handed down from generation to generation, so that one of a sutradhar's sons will take over the leadership of the troupe after his father. The sutradhar's leadership is absolute; he is the troupe's most important singer and puppeteer. The puppets represent the troupe's capital, as the members do not as a rule have other employment or own land. The renown of the sutradhar and thereby of the troupe may depend on his ability to improvise. Improvisation comes into its own in the comical intermezzos, where the clowns in the play, Kilikayata and Bangaraka, in comical scenes differing essentially from the heroic episodes which form the main theme of the performance, comment on life in the village by means of gesture and action (fig. 14). H. K. Ranganath, in The Karnatak Theatre, 1960, finds in these grotesque scenes vestiges of an ancient fertility cult. The ritual significance of the shadow play may be experienced to this day. It is considered to be lucky to attend performances, especially in April during the celebrations for Siva, the patron god of the shadow play. At some places, performances are given in honour of the patron god of the village, to ensure regular rainfall. The story derives mainly from the Ramayana and the Mahabharata. A troupe has 6-10 different plays in its repertoire for which rehearsal is unnecessary; its members have a lifelong experience in song, instrumental music, dialogue and improvisation. The most popular play, called »Lanka Dahanam« in Telugu, deals with Sita's release from her imprisonment on Lanka (Ceylon). Songs, dialogue and improvisation are in Telugu, but it is not unusual for the sutradhar to show off his literary knowledge by adding verses in Sanskrit. The following describes the course of a performance in Dharmarao Cheruvupalli in the district of Nellore, 29.3.1970, in which oil lamps were used. 3 p.m.-8 p.m. Four male members of the troupe erect the platform in front of the Siva temple (fig. 15). It is supported by four 7 m high corner posts (fig. 17). 9 p.m. The beginning of the performance is announced with the dappulu drum. 9.20 p.m. The opening prayers to Siva are recited in the booth. 9.30 p.m. The oil lamps are lit. The god Ganesh is shown and his praises sung. 9.40 p.m. The goddess of knowledge, Saraswathi, dances. 9.55 p.m. Comic intermezzo, Kilikayata and Bangaraka. Improvisation directed at all the village households. 10.30 p.m. The theme is introduced. The heroes Rama, Laksmana and Sita first appear. This is followed by a rapid shift to the world of the demons in Lanka. The main action consists of a series of linked episodes in which the world of the heroes and the world of the demons are shown alternately. The positive and negative powers are contrasted in impressive battle scenes. The true hero in this play is the monkey god Hanuman who finally overcomes the demon king. 4.45 a.m. The performance ends with the singing of thanksgiving hymns. Niels Roed